Variação do canto de Thamnophilus Doliatus (Linnaeus, 1764) (Aves: Thamnophilidae) em diferentes regiões da América Latina - Catalano, Ana Luiza Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to analyze and to compare vocalizations of individuals of the species Thamnophilus doliatus from different locations of Latin America. 280 loudsongs from 140 individuals were analyzed and the variables taken into account were the following: number of notes, duration of the sequenced patch, note rate (notes per second), overall peak frequency, duration of the terminal note, and peak frequency of the terminal note. The loudsongs were also divided into portions in order to measure the variation of note rate (speed) and pitch (frequency) along the patch. The loudsong characteristics were correlated with geographic factors such as latitude, longitude and altitude to check if there is any acoustic pattern with the location. Also, the sample was clustered into subspecies for comparisons. The analyzed variables were strongly correlated with latitude, where individuals from equatorial locations had loudsongs with more notes, longer in duration, faster in note rate and a terminal note lower in peak frequency. The variables also appeared to be significantly correlated with longitude, including as well the overall peak frequency. Seven subspecies were identified according to their locations, however, only five of them were used for comparisons. Results showed a separation of the intermedius and radiatus subspecies due to their significant divergence in number of notes, patch duration, note rate and peak frequency. Comparisons with the recently separated species Thamnophilus capistratus were also made and no significant variation were found in the number of notes and total duration, but there were differences in note rate, overall peak frequency, peak frequency and duration of the terminal note. Because song characteristics between the different species (T. doliatus and T. capistratus) presented to be more similar than among the subspecies of T. doliatus, raises the question of the existence of more than one species within ...

Este trabalho teve como objetivo analisar e comparar as vocalizações entre indivíduos e subespécies de Thamnophilus doliatus de diferentes localizações da América Latina. Foram analisados 280 cantos de 140 indivíduos diferentes, e as variáveis levadas em consideração foram: número de notas, duração do trecho em sequência, taxa de notas por segundo, frequência de pico total do trecho, duração da nota terminal e frequência de pico da mesma. Os cantos também foram divididos em porções para se calcular a variação de velocidade e de tonalidade (frequência) ao longo dos trechos. As características do canto foram correlacionadas com dados geográficos como latitude, longitude e altitude a fim de se conferir se existe alguma padronização com a localização, e a amostra também foi agrupada em subespécies de acordo com suas localizações para comparações. As variáveis analisadas foram fortemente correlacionadas com a latitude, indicando que indivíduos de localização equatorial emitem cantos com mais notas, mais longos, mais rápidos e com uma nota terminal mais grave do que aqueles localizados ao sul da distribuição. As variáveis também foram correlacionadas com a longitude, incluindo também a frequência de pico. Foram identificadas sete subespécies de acordo com as localidades em que foram gravadas, porém apenas cinco foram utilizadas para comparações. Resultados mostraram uma separação das subespécies intermedius e radiatus pelas significativas diferenças no número de notas, duração do trecho, taxa de notas por segundo e frequência de pico. Também foram feitas comparações com a recém-separada espécie Thamnophilus capistratus, e só foram encontradas diferenças significativas na nota terminal e na variação de frequência ao longo do trecho. Devido às características do canto se mostrarem mais próximas entre diferentes espécies (T. doliatus e T. capistratus), que entre as subespécies de...
Keywords: Ave - Vocalização; Pássaro; Pesquisa ornitologica; Bioacustica; Animais - Sons; Taxonomia numerica; Birds - Vocalization